Analisis Pengaruh Penambahan Gardu Induk Terhadap Aliran Daya dan Profil Tegangan - Sri Wahyuni Dali; Imron Ridzki; Rohmanita Duanaputri; Egar Rahmat Maulana (Elposys: Jurnal Sistem Kelistrikan, 2022)
Addition of the Guluk-Guluk Substation, it will affect the flow of power and voltage in the electric power system. Based on the analysis of normal conditions before and after the Guluk-Guluk Substation in terms of the voltage value on each connected bus, it is still within the permitted limits, while the contingency ranking calculation using the Voltage Performance Index (PIv) method can determine contingency conditions N-1 to N -3 before and after the Guluk-Guluk Substation. In this case, it was found that during the contingency conditions N-1 to N-3 before the Guluk-Guluk Substation there was a decrease in the value of the voltage which was still within the permissible limits, but in the N-3 contingency there was also an overload on the line due to the release of two generator units and one channel. After the existence of the Guluk-Guluk Substation, during the N-1 to N-2 contingency conditions the voltage value was still within the permissible limits, but the voltage drop that occurred was bigger than the condition before the Guluk-Guluk Substation. For the N-3 contingency condition the voltage value does not meet the standard due to overload on the Ujung Substation - Bangkalan Substation line and the lack of power flow.